Analysis of long-term wheat varieties for climate resilience and productivity oscillation in different environments of India - Mohan, D. (The Indian Journal of Genetics and Plant Breeding, 2016)
Six long-term wheat cultivars of India were examined for the period 1993-2012 to observe climate induced variations in productivity and growth pattern. Each cultivar represented a particular environment manifested by a specific agro-climatic region and production condition, productivity of which was derived from 6-10 fixed locations.Significant yield fluctuations in majority of the environments indicated that climatic conditions were changing in different parts of the country. Trend in yield change appeared cyclic and site differences also turned larger in certain situations. Pattern of climate induced yield variations depended upon region and production condition as the extent was high in late-sown wheats in comparison to timely-sown and less in the Indo-Gangetic plains in comparison to central-peninsular India. Disparity occurred within Indo-Gangetic plains also, as yield fluctuated more in the eastern region. Direction of change varied in different environments as yield decelerated in late-sown wheats of Indo-Gangetic plains and enhanced in harsh climate of central-peninsular India. Crop growth during vegetative phase turned favourable in central-peninsular India whereas reduction in grain ripening period was evident in northeastern plains. Linear trends and magnitude of variations in yield cum component traits were applied to demarcate differences in varietal response. Level of climate resilience differed in the study material and two cultivars namely HUW 234 and LOK 1 appeared climate resilient.